1992
DOI: 10.1007/bf02385008
|View full text |Cite
|
Sign up to set email alerts
|

The tumor promoter pristane activates transcription by a cAMP dependent mechanism

Abstract: Pristane is a naturally occurring isoprenoid which is believed to be derived from the phytyl moiety of chlorophyll. Thus it is not surprising that pristane is present in many common fruits or vegetables and furthermore can be detected in tissues of fish and mammals. Using the rat as an animal model, pristane can function as a potent tumor promoter. It is conceivable that pristane could play a role in the development of certain malignancies in higher mammals since it is commonly found in the diet. At the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Several studies have demonstrated that pristane activates transcription and that a CRE appears to be a primary target for transcriptional activation by pristane [21,22,30]. These studies demonstrate point mutations in the CRE eliminated activation ( Figure I), suggesting that proteins binding a functional CRE were activated when cells were treated with pristane.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Several studies have demonstrated that pristane activates transcription and that a CRE appears to be a primary target for transcriptional activation by pristane [21,22,30]. These studies demonstrate point mutations in the CRE eliminated activation ( Figure I), suggesting that proteins binding a functional CRE were activated when cells were treated with pristane.…”
Section: Discussionmentioning
confidence: 82%
“…In large part, adenyl cyclase, phosphodiesterase, and PKA regulate CRE-dependent transcription [23,24,4143]. Because pristane activates CRE-dependent transcription [22,30] (Figure I), the levels of these enzymes were measured after P+ or P-cells were treated with pristane. In P+ and P-cells, the levels of adenyl cyclase activity were similar to those in control cells (data not shown).…”
Section: Jb6 Cells With Pristanementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the extracts C3 and D3 exhibited presence of pristane. Previous studies reported various bioactivities of these compounds, such as cytotoxic and antitumour potential of TQ [21,41], thymohydroquinone [55,56] and pristine [57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pristane exhibited tumor enhancing properties in our Copenhagen rat model in which direct Peyer’s patches (PP) injection with a low dose of 3-methylcholanthrene (3-MC) led to only B lymphoid malignancies, a high 3-MC dose treatment induced thymic lymphomas but no B cell malignancies, and co-treatment with 3-MC and pristane lead to higher frequency and decreased latency of 3-MC induced lymphoid malignancies [ 9 ]. Also, pristane elicited marked effects on transactivation of transfected genes [ 10 13 ]. These activities are comparable to 12-O-tetradecanoylphorbol 13-acetate (TPA), a known tumor promoter [ 14 ].…”
Section: Introductionmentioning
confidence: 99%